SISTEM INFORMASI PADA SATUAN PAUD SEJENIS (SPS)PAUD ANGGREK 05 BERBASIS WEBSITE - Dheasy Nurfadhilah (2023)
Current technological developments, educational institutions are emphasized to be able to take advantage of increasingly rapid technological developments. The development of website-based information systems has been widely applied in several fields, including in the field of education. Easy access only by using the internet which can provide information accurately and quickly by using the website. SPS PAUD Anggrek 05 is an early childhood education institution. This PAUD was founded in 2006. During the past pandemic, the problem with PAUD Anggrek 05 was the lack of group study rooms (classes) due to the lack of socialization and delays in face-to-face activities at school. School registration which was carried out directly and manually at PAUD Anggrek 05 was considered less effective considering the conditions at that time After a pandemic like now, teaching and learning activities are carried out face-to-face. So for making a website-based information system at SPS PAUD Anggrek 05 it is very necessary. In this study the analysis used by the author is PIECES analysis (Performance, Information, Economic, Control, Efficiency and Service) and the author uses a method, namely the waterfall method with sequential flow namely analysis, design, programming (coding), testing (testing), and maintenance (maintenance). The information system was built using Visual Studio Code for coding and using Figma to create a User Interface (UI). The results of the system can help and simplify the registration process and help make it easier for teachers to manage and store student data and make it easier for people who will register their children to school by knowing some teacher or educator assessments, school assessments, activities carried out during the learning period and what achievements have been achieved by SPS PAUD Anggrek 05 students.